PERAN PENDIDIKAN VOKASIONAL DALAM ERA DIGITAL - Nadif Maialfatih (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
Education is an important component for the progress of a country. The more adequate and developed education, the more advanced the society. Education and technology must be able to go hand in hand. In the digital era, the process of change and development certainly goes very fast. This process was initially marked by advances in technology which greatly influenced human life, including education or vocational education. Vocational education or vocational education is also known as vocational education at the SMK/MAK level, which is education at a high level which aims to prepare students to continue to higher levels of education and/or expand basic education, as well as to improve students' abilities to be able to develop themselves in line with the development of science, technology and the arts, so that they can enter the workforce and develop a professional attitude